Synthesis of pyrazole-containing xyloketal-like compounds - Mrug, Galyna; Bondarenko, Nataliia; Bondarenko, Svetlana; Frasinyuk, Mihaylo (My University, 2018)
Unique metabolites named xyloketal A – H which containing fused bezopyran and furan rings with acetal function were Isolated from mangrove fungus Xylaria sp.The biosynthesis and chemical syntheses of these and related compounds are based on inverse-electron-demand Diels-Alder reaction. We developed synthesis of pyrazole derivatives of 2,3,3a,9a-tetrahydro-4H-furo[2,3- b]chromene heterocyclic system which presents in natural acetals. Interaction of thermally generated ortho-quinone methides from isoflavone Mannich bases with 2,3- dihydrofuran or 3,4-dihydro-2H-pyran led to formation fused acetals. Selective cleavage of pyranone ring compounds by hydrazine treatment led to the formation of xylokeketal-like–pyrazole hybrids

Унікальні метаболіти під назвами ксилокеталь A – H, які містять конденсовані безопіранові та фуранові кільця з ацетальною функцією, були виділені з мангрового гриба Xylaria sp. Біосинтез і хімічний синтез цих та споріднених сполук базуються на реакції Дільса-Альдера з оберненими електронними вимогами. Розроблено синтез похідних піразолу гетероциклічної системи 2,3,3a,9a-тетрагідро-4Н-фуро[2,3-b]хромену, яка представлена в природних ацеталях. Взаємодія термічно генерованих орто-хінон-метидів з основ Манніха ізофлавонів з 2,3-дигідрофураном або 3,4-дигідро-2Н-піраном призвела до утворення ацеталів. Селективне розщеплення піранонового кільця обробкою гідразином привело до утворення ксилокеталь-піразольних гібридів
Keywords: xyloketal; inverse-electron-demand Diels-Alder reaction; pyrazole; ксилокеталь; реакція Дільса-Альдера з оберненими електронними вимогами; піразол; кафедра харчової хімії